FEASIBILITY OF SCHOOLOGY-BASED BLENDED LEARNING MEDIA IN RESPIRATORY SYSTEM OF XI GRADE TO TRAIN SCIENTIFIC LITERACY SKILL - Risa Fitria; Sifak Indana (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Abstract Scientific literacy is the ability to use knowledge, identify problems, draw conclusions, and make decisions. Scientific literacy is trained through scientific experiments. Scientific experiments take a long time because students must understand the concept and orientation of the problem, carry out practical activities, and analyze data, hence there is a need for learning that can meet those needs. One solution is to use blended learning. The aim of this research was to describe the feasibility of media Schoology-based blended learning in the respiratory system of XI grade based on validity, practicality, and effectiveness to train scientific literacy skill. This research was developmental research used the Research and Development (R & D) model which consisted of problem and potential analysis, data collection, product design, product design validation, product design revision, product testing, and 1st product revision. Limited testing done in 20 XI grade students of SMA Negeri 1 Kedungpring. The research instruments used were learning media validation sheets, observation sheets of student activities, evaluation test sheets, student response sheets, and activity sheets for scientific literacy skills. The research data were analyzed descriptive quantitatively. The results showed that the learning media developed was very valid with a score of 3.88. Learning media was very practical based on the activities of students with a percentage of 93.19% and practical based on the activities of scientific literacy skills with a score of 80.5. Learning media was effective based on the results of learning completeness with a percentage of 80%, effective based on the achievement of learning indicators with a percentage of 75%, and very effective based on student responses with a percentage of 97.94%. Keywords: scientific literacy; respiration system; blended learning; schoology